Details men's style manual : : the ultimate guide for making your clothes work for you - Peres, Daniel (New York : s.l. :: Gotham Books: Melcher Media, 2007)
A guide to men's fashion offers advice for such topics as selecting formal wear, outerwear, and accessories, and includes fashion and style tips by celebrities, including Giorgio Armani and Sean Combs.
Shirts: Three degrees of the well-dressed man -- Pants: Rules of style: Giorgio Armani -- Blazers: Map of the well-dressed man -- Ties: Rules of style: Michael Kors -- Suits: Know the code -- Formalwear: Rules of style: Sean Combs -- Jeans: Rules of style: Tommy Hilfiger -- Casual shirts: Rules of style: Donna Karan -- Sweaters: the movies that shaped men's style ; Rules of style: Christopher Bailey -- Outerwear: Rules of style: Zac Posen -- Underwear: Rules of style: Kenneth Cole -- Shoes: Rules of style: Donatella Versace -- Accessories -- How to pack -- How to care for your wardrobe -- Where to shop.
Keywords: Men's clothing; Men's clothing